Association between the histopathologic findings of a zero-time biopsy and the donor kidney function 24 hours and a year after nephrectomy - Arreola, Karla I. Zarco; Gonzales, Israel D. Campos; Chagolla, Blanca J. Martinez; Pérez, Jorge A. Quiroz; Luna, Luis E. Suarez (International Journal of Research in Medical Sciences, 2022)
Background: The living-donor transplantation (LDT) is essential to provide patients with chronic kidney disease (CKD) a superior quality of life and improve their lifespan. Recent investigations prove that the living donors (LD) have a risk of developing CKD, without there being a way to anticipate it. The zero-time biopsies provide valuable information that may contribute to this objective since they report histopathologic findings of subclinical chronic damage. Methods: Retrospective, observational and analytical study. The information from the medical files and pathology department of LD attended at “Dr. Miguel Silva” general hospital from January 2006 to January 2018 was analyzed. The glomerular filtrate rate was obtained 24 hours and a year after nephrectomy and was estimated based on CDK-EPI. The comparison among groups was made through Mann-Whitney testing for continuous numeric. A value of p<0.05 was considered statistically significant. Results: A total of 56 medical files were studied, 29 of which had a report of biopsy, the general prevalence of histologic anomalies was 65%. We found that those patients that showed a lower value in the GFR after 24 hours also showed lower GFR the next year, likewise a narrow and statistically significant correlation between the creatinine levels in the immediate post-operative period and the following year was found. In the same way, we found that the higher the dropping rate of GFR after 24 hours of nephrectomy, the lower the GFR a year after donation being statistically significant. It was decided to divide the sample into two groups (with and without histological alterations), it was found that a year later the GFR in the group with histological damage was less (75.6±21.7 ml/min/1.73 m2) compared to the group without damage (85.2±11.6 ml/min/1.73 m2) with a p<0.05 (Figure 4) and finally, there is association between the age group and the GFR the year after donation. Conclusions: Among the candidates for LDT, the zero-time biopsy alterations, the age >36 years, the dropping of the GFR >43%, the GFR and the creatinine levels after 24 hours of nephrectomy were associated with a reduction of the GFR the year after nephrectomy.